The Gold and the Clay : Confluence of Traditions. - Barolo, Agnese; Bezzi, Daniela; Jain, Jyotindra; Jain, O.P.; Mantica, Clara; Poncini, Giovanni; Tarshito; Tyabji, Laila (New Delhi : The Crafts Museum, 2001)
Tarshito ; Singh, Amar ; Jana, Sanjay ; Jagdish, Lala ; Kumar Pandit, Shekhar ; Ram Prajapati, Bihari ; Bai, Ganeshi ; Bai, Sundari ; Sharma, Ashok & Deepak ; Devi, Mira ; Kumar, Khaidhya ; Narayan Marotia, Hari ; Kalavati ; Khatun, Alima ; Chandra Maharana, Purna ; Tyabji, Laila ; Chanda ; Lalita ; Ara, Nusrat ; Ben, Mangu ; Ben, Lila ; Ben, Bhavna ; Ben, Kakku ; Subadhra ; Bai, Gauri ; Bai, Parvati ; Bai, Kasi ; Seethavva, Sanna ; Hemavathi ; Bai, Devi ; Sharma, Rohit ; Sarmah, Debojit
Engels
The Gold and the Clay : Confluence of Traditions, The Crafts Museum, New Delhi, March 24 - May 31, 2001 + org. Ministry of Textiles, Govt. of India, Italian Embassy Cultural Centre
boek
Keywords: Indië; Italië